Religious Social Communication for the Conservation of the Riverbank Area - Mohammad Taufiq Rahman; Bukhori Bukhori (Jurnal Iman dan Spiritualitas, 2022)
This research shows that environmental problems in community development are still not fully resolved. For the Citarum River case, the government has already implemented the Harum Citarum Program. However, the local community itself determines whether or not the watershed is maintained. For this reason, educational and communication efforts from various parties concerned about this problem are necessary. Included in this are the clergy and religious communication. This is because the local community is religious. This sociological study explores public opinion on raising awareness of environmental literacy with a religious approach.